Effect of baseline values on inpatient rehabilitation outcomes after total knee arthroplasty: a retrospective observational study - Martin Missmann; Michael J. Fischer (Journal of Rehabilitation Medicine)
Objective: To compare inpatient rehabilitation outcomes after total knee arthroplasty (TKA) between groups with different baseline scores.